2000
DOI: 10.1002/1097-0320(20001101)41:3<172::aid-cyto3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell heterogeneity and subpopulations in solid tumors characterized by simultaneous immunophenotyping and DNA content analysis

Abstract: Background Heterogeneity in human malignant tumors is a well‐described phenomenon and of interest with regard to subpopulations with differences in clonality, metastatic potential, and response to therapy under different treatment regimes. The aim of this study was the simultaneous characterization of surface markers and DNA content of solid tumors to identify tumor cell subpopulations and to study the association between the expression of antigens and DNA content. Methods In the present study, six different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Further divergence of the clone may result in subpopulations of neoplastic cells, some of which gain the capacity to metastasize. [13][14][15][16][17] Although genetic heterogeneity is the norm in melanoma, [18][19][20][21][22] it would be expected that a primary melanoma and its metastases would share at least one or more genetic alterations. Studies to date have shown that loss of heterozygosity (LOH) on 9p and 10q has been associated with early-stage primary disease, whereas LOH on 6q, 1p, 8q, and 11q has been associated with progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Further divergence of the clone may result in subpopulations of neoplastic cells, some of which gain the capacity to metastasize. [13][14][15][16][17] Although genetic heterogeneity is the norm in melanoma, [18][19][20][21][22] it would be expected that a primary melanoma and its metastases would share at least one or more genetic alterations. Studies to date have shown that loss of heterozygosity (LOH) on 9p and 10q has been associated with early-stage primary disease, whereas LOH on 6q, 1p, 8q, and 11q has been associated with progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic divergence after clonal expansion may lead to the development of several subpopulations of neoplastic cells with only rare cells gaining the capacity to metastasize. 11,12,15,23,29 Examinations of subpopulations of tumor cells within a number of malignancies have shown that many types of tumors exhibit tremendous genetic heterogeneity. Whether metastases derive from a single clone which populates the majority of the primary tumor or whether metastases arise from a small, minority of cells with a divergent genetic makeup and with the capability of metastasis is uncertain.…”
mentioning
confidence: 99%
“…However, as reported by Yordanov et al, a small decrease in the delivery efficiency of the loaded polymeric nanocapsules may be a consequence of partial erosion of PBCA nanocapsules (42). Additionally, some differences in uptake may be related to a discrepancy in divisional state of the cells or be caused by cell heterogeneity of the used tumor cell lines (43,44). Further studies are needed to clarify this problem.…”
Section: Facs Fluorescence Detection Of Cyanine Ir-780 Delivered Withmentioning
confidence: 89%